Association between BACE1 gene polymorphisms and focal seizures in a Chinese Han population. Issue 13 (March 2018) - Yang, Guangsheng; Wang, Haidong; He, Xin; Xu, Pengfei; Dang, Ruili; Feng, Qingyan; Jiang, Pei
Abstract: Background: Beta-secretase 1 (BACE1) is attracting increasing attention for its vital role in pathogenesis of many neuropsychiatric disorders and many studies also have indicated BACE1 as a possible risk factor for seizures, but not any studies have reported association between BACE1 gene polymorphisms and seizures. Therefore, we investigated the possible association between focal seizures and BACE1 gene polymorphisms in the present study. Methods: A total of 162 patients and 211 health controls were enrolled in this study and polymorphisms of BACE1 gene were detected using polymerase chain reaction (PCR)-ligase detection reaction method. Results: The frequency of genotype AT for BACE1 rs535860 (A>T) was significantly higher (24.1%) in patients compared to controls (14.7%) (OR = 1.836, 95% CI = 1.086–3.102, P = .023). Intriguingly, we only found the significant difference of BACE1 SNP genotype and allele frequency among males but not females. However, no statistically significant results were presented for the genotype distributions of rs525493 (G>T) and rs638405(C>G) polymorphisms between patients and controls. Conclusion: Our study demonstrated there may exist an association between BACE1 rs535860 (A>T) polymorphism and focal seizures in Chinese Han males.